INTERNATIONAL AND NATIONAL LEGAL ASPECTS OF THE PRINCIPLE OF CHILDREN'S SURVIVAL AND DEVELOPMENT - Allahverdiyev Zamiq Namik, (International Journal of Innovative Technologies in Social Science, 2024)
The formation of the need for the special protection of children and the recognition of their rights came to the fore as a result of the historical processes taking place in the world. In the article, the factors determining the international and national legal protection of the principle of children's survival and development have been studied from various aspects. As a result of the comparative analysis, the article clarified the problems encountered during the application of international and national legal norms in the field of the principle of children's survival and development, and presented suggestions and recommendations. As a result of the conducted research, in addition to presenting proposals for the elimination of existing practical and legal problems, analyses of the norms of domestic regulation were also conducted.